Investigating the chemistry of pyridinium ylides - Abdullah, Rasha Azzam (2018)
This thesis describes investigation into catalytic formation of pyridinium ylides from diazo compounds and their subsequent reactivity. In particular, cycloaddition reactions with electrophilic alkenes are performed to generate tetrahydroindolizines that can be transformed into indolzidines by reduction. Pyridinium ylides have been shown to be very reactive intermediates that are able to generate complex molecules with excellent yield and diastereoselectivity. The introduction section provides a background on the chemistry of pyridinium ylides. This section also reports on development in the field of 1,3-dipolar cycloaddition chemistry of pyridinium ylides. A background to the generation of the pyridinium ylides by in situ decomposition of diazo compounds with transition metal catalysts was described. The results and discussion section is divided into three sections. Section one describes metal-catalysed decomposition of diazo compounds to produce pyridinium ylides in situ. Performing this reaction in the presence of dipolarophiles gives tetrahydroindolizine cycloadducts in good yield with excellent diastereoselectivity. Subsequent reduction of the 1,2-dihydropyridine moiety component of the resulting cycloadducts is also demonstrated. Crystal structures of some of the resulting indolizidine products were valuable for assigning relative stereochemistry. Section two describes attempts towards an asymmetric (3+2) dipolar cycloaddition, using pyridinium ylides produced by the in-situ decomposition of diazo compounds with either chiral transition metal catalysts or achiral catalysts in the presence of chiral Brønsted acids. We started our investigation by exploring how acids with various pKa’s e.g. camphorsulfonic acid, benzoic acid and p-nitro benzoic acid influenced the reaction between pyridine and diazo compounds. Finally, section three describes attempts to develop new multicomponent catalytic reactions with mono and di-substituted diazo compounds to access structurally complex pyridinium salts via in situ C-alkylation of catalytically generated pyridinium ylides.